Capitalist spatiality in the periphery: regional integration projects in Mexico and Turkey - Erol, Ertan (2013)
This work aims to provide an alternative analysis of the regional economic integration and development projects of two peripheral capitalist spaces – Mexico and Turkey – within the specific spatiotemporal conditions in which their modern peripheral capitalist spatiality has been conditioned and re-structured. Both Mexico and Turkey undertook very similar regional integration projects that emerged almost simultaneously and, more significantly, in conjunction with the neoliberal restructuring processes that unfurled during the early 1980s. In the Central American region, Mexico initiated the ‘Plan Puebla-Panamá’ which subsequently evolved to the ‘Proyecto Mesoamérica’, now including Colombia, aiming to ‘create’ an integrated region with a high level of economic development on the basis of procuring sustainable and orderly functioning free market economies. With strikingly similar objectives, Turkey planned and materialised regional integration projects such as the organisation of the ‘Black Sea Economic Cooperation’ in the Black Sea and Trans-Caucasus region and other sub-regional projects such as the ‘Levant Project’ in the East Mediterranean.